2022
DOI: 10.34172/jcs.2022.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music on Pain, Anxiety and Physiological Parameters among Postoperative Sternotomy Patients: A Randomized Controlled Trial

Abstract: Introduction: Music is a non-invasive, inexpensive and non-pharmacological nursing intervention that has no side effects and can be effective when provided alongside the routine care in cardiothoracic and vascular surgery (CTVS) ward and intensive care unit (ICU). The objective of the study was to assess the effect of music on pain, anxiety and physiological parameters among the post-operative sternotomy patients from CTVS ward and ICU in Jawaharlal Institute of Postgraduate Medical Education and Research (JIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The mean (SD) age of the participants in the experimental and control groups was 38.73 and 42.83 years, respectively. Most of the patients were married in the experimental group 60 (18) and in the control group 70 (21). The majority of patients in the experimental group 70 (21) and the control group 63.3 (19) had no history of hospitalization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean (SD) age of the participants in the experimental and control groups was 38.73 and 42.83 years, respectively. Most of the patients were married in the experimental group 60 (18) and in the control group 70 (21). The majority of patients in the experimental group 70 (21) and the control group 63.3 (19) had no history of hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the patients were married in the experimental group 60 (18) and in the control group 70 (21). The majority of patients in the experimental group 70 (21) and the control group 63.3 (19) had no history of hospitalization. In addition, concerning the type of surgery, the majority 83.3 (25) underwent surgery in the femur area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled trial (RCT) of 70 postoperative sternotomy patients revealed a marked reduction in the pain scores in the patients in an intervention group compared to a control group. [22] The present study also analyzed the effect of music as an adjuvant on physiological parameters (vital signs) such as systolic blood pressure, diastolic blood pressure, heart rate, and respiratory rate. There were no statistical mean differences of these parameters between intervention and control groups before and after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Finally, it can be said that the health care providers and families tend to use traditional medicine treatments based on their culture. 47 The health care providers try to adjust their culture using scientific resources, but the families use their cultural values as the basis of their practice.…”
Section: Discussionmentioning
confidence: 99%